Effect of melatonin on follicular development parameters in a fixed-timed artificial insemination programme in water buffalo - Berdugo, Jesus Alfredo (Array, 2021)
It is well known that buffaloes have seasonal anoestrus and that the use of melatonin reduces the effects of season in reproduction, articularly among sheep and goats. This study evaluates the use of melatonin on water buffaloes to increase pregnancy rates in a fixed-time insemination programme. The study was conducted on an Argentinian buffalo herd, located in the Corrientes Province, during an unfavourable reproductive season. Artificial insemination cycles were performed in September and December 2018. Sixty animals were selected, and melatonin was administered to 29 females at a dose of 18 mg/50 kg. Ten days after the melatonin implant, ovulation synchronization was started. Animals were inseminated with frozen semen of a single bull. Pregnancy was evaluated by ultrasound 35 days after insemination. The pregnancy rate of the two repetitions was 34.62% for September and 6.4% for December (P=0.007). No significant differences were found in the parameters associated with follicular development and formation of the corpus luteum. Analysis of the effects of melatonin on the two replicates showed that there was no statistically significant effect of ovarian response regarding the analysed follicular development parameters. There was also no effect on pregnancy rates (17.85% vs. 20.68%; P=0.15), or on follicular development for treatment and control. In conclusion, this study was not able to demonstrate an effect of melatonin on the ovarian response of buffaloes as reported by other authors. Other factors, such as environmental conditions of subtropical areas and species specificities, may have a more significant effect on buffalo endocrinology. These factors should be evaluated to improve the results of fixed-timed artificial insemination programmes.